"AMERICAN IDIOT": EXAMINING READERS' SUBJECT POSITION IN ONE OF GREEN DAY'S ALBUMS - Supardan, Admiral Indra (2013)
ABSTRAK Kajian penelitian ini berjudul "American Idiot": Examining Readers' Subject Position in One of Green Day's Music Albums. Tujuan penillitian ini adalah menganalisa cara-cara yang dikembangkan di album keenam dari Green Day, American Idiot (2004), dalam memposisikan pembaca yang dituju (implied reader) secara ideologis, untuk menentang agenda politis Amerika Serikat. Adapun metodologi yang digunakan dalam kajian ini adalah kualitatif deskriptif. Tiga kerangka teori yang digunakan untuk menganalisa album yang terdiri dari 13 lagu ini adalah: ideological analysis oleh John Lye (1997), context framework olehAdrian Beard (2001), dan John Stephens' (1992) narrative transactions-yang menempatkan implied reader sebagai fungsi ideologis di dalam sebuah teks. Dengan menggunakan teori tersebut, kajian ini mengemukakan bahwa ada lima isu kultur-sosial yang diyakini sebagai upaya untuk memposisikan implied reader, untuk menentang agenda politis Amerika Serikat pada masa pemerintahan Bush. Asumsi atau isu-isu ini dikenal sebagai posisi subjek (subject position), dan secara ideologis ditawarkan kepada implied reader menggunakan alat yang dikenal sebagai aspek-aspek narasi, yakni: sudut pandang cerita (point of view) dan pembawa cerita(narrator). Kata kunci: implied author, implied reader, subject position, ideologi, narrative. ABSTRACT This research paper entitled "American Idiot": Examining Readers' Subject Position in One of Green Day's Music Albums is aimed at investigating the ways by which the sixth album of Green Day, American Idiot (2004), ideologically positioned the implied readers in opposite to the USA political agenda. A qualitative descriptive study is employed in this present study. In analyzing the album, which consists of 13 songs, three theoretical frameworks are used: ideological analysis by John Lye (1997), context framework by Adrian Beard (2001), and John Stephens' (1992) narrative transactions-where he locates the implied readers as the ideological function of a text. By having those frameworks within the analysis, the study discovers five socio-cultural issues, recognized as an attempt to position the implied readers in opposite the US political agenda in Bush administration. These assumptions within the issues known as a subject position are ideologically offered to the readers or the implied readers through narrative aspects; point of view and narrator. Keywords: implied author, implied reader, subject position, ideology, narrative.